Pharmacological interventions for social cognitive impairments in schizophrenia: A protocol for a systematic review and network meta-analysis - Yamada, Yuji; Okubo, Ryo; Tachimori, Hisateru; Uchino, Takashi; Kubota, Ryotaro; Okano, Hiroki; Ishikawa, Shuhei; Horinouchi, Toru; Takanobu, Keisuke; Sawagashira, Ryo; Hasegawa, Yumi; Sasaki, Yohei; et al. (Frontiers in Psychology, 2022)
Background: Social cognitive impairments adversely affect social functioning (e.g., employment) in patients with schizophrenia. Although pharmacological interventions have been suggested to provide some benefits on social cognition, little information is available on the comparative efficacy of pharmacotherapy. Thus, the aim of this planned systematic review and network meta-analysis is to perform a quantitative comparison of the effects of various psychotropic drugs, including supplements, on social cognition disturbances of schizophrenia. Methods: The literature search will be carried out using the PubMed, Embase, Cochrane Central Register of Controlled Trials, PsycINFO, ClinicalTrials.gov, and International Clinical Trials Registry Platform databases from inception onward. Randomized controlled trials that examined the efficacy of drugs in social cognitive disturbances will be included, based on the most recent studies and the broader literature than previously searched. This protocol defines a priori the methods that will be used for study selection, data collection, quality assessment, and statistical syntheses. Discussion: The findings of this systematic review and network meta-analysis are expected to help promote the development of better therapeutics of social cognitive impairments in schizophrenia and related psychiatric conditions. Systematic Review Registration: PROSPERO (registration number is CRD42021293224)